Effectiveness of Acupuncture Therapy Combination with Moringa Leaf Mask on the Degree of Acne Vulgaris Lesions in Students of the Acupuncture Department of Surakarta Health Ministry Polytechnic - Mufidah, Hilyatul Ilmi Al; Putri, Kurnia Eka; Widyawaty, Eka Deviany (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Acne Vulgaris is a disease condition that causes inflammation of the skin area in the form of blackheads, papules, pustules, and nodules. The prevalence of acne vulgaris in Indonesia is third ranks with more than 85% experienced by teenagers. The research method with Quasi-Experimental Pretest-Posttest two-group designs with a total sampling technique with 38 respondents. In this study was divided into two groups, group I acupuncture therapy with local facial points combined with moringa leaf masks and group II acupuncture therapy with local points LI 4 Hegu, LI 11 Quchi, ST 36 Zusanli combined with moringa leaf masks. The degree of acne vulgaris lesions was measured before and after 10 treatments.This research was conducted at the Acupuncture Department of Surakarta Health Ministry Polytechnic from February 5, 2024, to March 11, 2024. The results of the Wilcoxon test showed significant changes in the degree of acne vulgaris lesions in groups I and II with a value of <0.05 (0.000). While the Mann-Whitney test obtained a Sig value. (2-tailed) p= 0.00. With an average change value in group I of 26.71 and group II of 12.29, it is concluded that acupuncture therapy with local facial points combined with moringa leaf masks is more effective than acupuncture therapy at points LI 4 Hegu, LI 11 Quchi, ST 36 Zusanli combined with moringa leaf masks on the degree of acne vulgaris lesions. The conclusion, acupuncture therapy with local facial point combined with moringa leaf masks showed effective results in reducing the degree of acne vulgaris lesions